Letter (copy) : Persecutions in Spain - Citrine, Walter, 1887-1983
013-0076-001 International. WMC/WJB/DT/962. 20th May, 1940. Mr. W. Carrillo, Bayswater Hotel, Bayswater Road, LONDON, W.2. Dear Mr. Carrillo, We duly received your letter with regard to Comrade Rafael Henche and Caballero's son, and will let you have any news as soon as it reaches us. In the meantime, we thank you for your observations with respect to the recent libel case and the activities of Communists in Spain and other countries. Yours sincerely, General Secretary. 292/946/13/76